What is the optimal prophylaxis against postoperative deep vein thrombosis in the living donor to avoid complications and enhance recovery? – A systematic review of the literature and expert panel recommendations. Issue 10 (9th December 2022) - Ruffolo, Luis I.; Levstik, Mark; Boehly, Jen; Spiro, Michael; Raptis, Dimitri A.; Liu, Linda; Hernandez‐Alejandro, Roberto; ,
Abstract: Background: Deep venous thrombosis (DVT) prophylaxis is often employed to prevent the potentially serious complication of pulmonary embolism (PE). However, little data exist regarding the optimal DVT prophylaxis strategy for living donors undergoing hepatectomy for living donor liver transplantation. Here we present our consensus statement on DVT prophylaxis for living donors undergoing hepatectomy. Objectives: To identify the optimal DVT prophylaxis strategy, which reduces, risk of complications in living liver donors, and enhances recovery. Methods: Systematic review following PRISMA guidelines and recommendations using the GRADE approach derived from an international expert panel. Of interest was the impact of DVT prophylaxis or lack of prophylaxis on living donors undergoing hepatectomy and subsequent rates of DVT, PE, and hemorrhagic complications. PROSPERO ID: CRD42021260720 Results: The review of the literature identified three studies, which directly addressed thrombogenesis following living donor hepatectomy. All studies were observational in nature without randomization into treatments. The rate of DVT‐PE in unscreened living donors with chemoprophylaxis was 5%. Furthermore, thromboelastography of living donors demonstrated sustained hypercoagulability for 50% of donors 10 days postoperatively. In line with CHEST (The American College of Chest Physicians) guidelines of chemoprophylaxis for surgical procedures with 3% or greater risk of DVT‐PE, we conclude that a minimum of 10 days of postoperative chemoprophylaxis with unfractionated heparin or low‐molecular weight heparin is recommended for patients undergoing living donor hepatectomy. The quality of evidence (QOE) for these recommendations based on the GRADE criteria is low, with a Grade of Recommendation of Strong. Conclusions: Chemoprophylaxis for DVT following living donor hepatectomy is associated with reduced adverse thrombotic events, (Quality of Evidence; Low | Grade of Recommendation; Strong).